An analysis on the effectiveness of music in advertising towards consumer's buying behavior - Ng, Pui Yue (2011)
Music is one of the most important elements in all the mass electronic advertising. Advertisers pick the right song that can best suit the product and brand carefully in order to get positive feedback from the consumers. Inappropriate match of music in the advertisement with the brand or product being advertised might lead to misinterpretation of the advertising message and it can be distractive at times. The primary focus of this study is to find out if music in advertising really effective towards the buying behavior of the students and young working adults. It is to develop a path model to explain how music works on the advertising and the effectiveness measures including attitude toward the advertisement and the difference of buying behavior. One hundred sets of survey questionnaires were distributed concerning on the effectiveness of music in advertising to youngster aged around eighteen to twenty-five. In-depth interviews were conducted in order to enhance the findings and also to get a more accurate result for this study. The result of this study will be able to reveal the impact of music in advertising and how much it can affect the consumers. As the researchers did the research, it is proven that music in advertising is really important and it does affect on consumers’ buying behavior. But however, the results from the research might not be fully accurate as the target audiences are only students of University Tunku Abdul Rahman and College Tunke Abdul Rahman with few random young working adults in Kuala Lumpur. It could not generalize the entire population of Malaysia. This research will be more accurate if it was done with wider group of respondents of different ages and places.